The carbon dioxide neutralizing effect of energy innovation on international tourism in EU-5 countries under the prism of the EKC hypothesis - Balsalobre-Lorente, Daniel (2022)
Mitigation of carbon dioxide emissions has become an utmost important global agenda, keeping into consideration the associated environmental hardships. As a result, it is important to unearth the factors which can neutralize carbon emissions to transform the world economy into a low-carbon one. Against this backdrop, this study explores the carbon dioxide neutralizing effects of economic growth, international tourism, clean energy promotion, and technological innovation in the context of five European Union (EU-5) nations during the 1990–2015 period. This study's main contribution is in terms of its approach to test the interaction effect between foreign direct investment (FDI) inflows and energy innovation on carbon dioxide emissions. The econometric analysis chronologically involves the employment of unit root, cointegration, causality, and regression methods. Overall, the findings support the inverted-U-shaped economic growth-carbon dioxide emissions nexus to verify the Environmental Kuznets Curve (EKC) hypothesis. Besides, the Pollution Haven Hypothesis in the context of the selected panel is also verified as higher FDI inflows are seen to boost the carbon dioxide emission levels. The results also confirm that energy innovation moderates the harmful effect of air transport (a proxy for international tourism) on carbon dioxide emissions during the developing stage of the tourism industry. On the other hand, renewable energy promotion is found to curb carbon dioxide emissions. These findings suggest that the European governments need to enhance investments in their respective renewable energy sectors and simultaneously ensure the development of clean industries, which can collectively help these nations become carbon-neutral in the future.